The performance of European Union countries in decoupling socio-economic progress from environmental impacts - Vintar Mally, Katja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2020)
Over the last few decades, the European Union has intensified its commitments to decouple socio-economic progress from resource use and environmental impacts. This article examines the performance of countries in implementing selected aspects of these commitments in the period 1990-2016. To this end, it focuses on the relationships between progress in human development, in particular in raising people's incomes, and pressures on natural resources and ecosystem services, as incorporated in the concept of ecological footprint. The results show a certain measure of success in decoupling the two among the countries of the European Union, but the same cannot be said of the world's countries more generally.
Keywords: človekov razvoj; ecological footprint; ekološki odtis; environmental protection; European Union; Evropska unija; human development; sustainable development; trajnostni razvoj; varstvo okolja